Influencing Companies’ Green Governance Through the System of Legal Liability for Environmental Infractions in China and Brazil: Lighting the Way Toward BRICS Cooperation - Wei, D.; Rafael, A. P. (BRICS Law Journal, 2023)
Peer-rewieved journal

Impacts of Policies and Infrastructure on the Usage of Electric Vehicles in Macao - Weng Chi Lei; Tai, On Teng (2023 Symposium on Environmental Science and Sustainable Technology (ESST2023), 2023)

Fintech Adoption: A Study of Users in the Guangdong-Macao In-Depth Cooperation Zone in Hengqin (China) - Weng, Chi Lei; Lampo, Alessandro (INTI JOURNAL, 2024)
Intended as an economic and development hub, the Hengqin Cooperation Zone aims to foster collaboration and integration between mainland China, Hong Kong, and Macao, serving as a platform for economic development and innovation among the three regions. The zone's development has increased demand for financial services, often offered through fintech. There is, however, a lack of interoperability between the fintech services currently used in Macao and Hengqin. This may hinder Macao users' adoption of the technology. Thus, our research objective is to identify the factors determining Macao residents' adoption of fintech services in the area and provide insights for service providers, developers, and policymakers. A framework based on the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) was used for this purpose. The responses of 103 Macao residents provided evidence that ease of use significantly and positively impacts the usefulness of the technology. This in turn influences attitudes towards fintech usage. Subjective norms and perceived behavioral control positively impact fintech adoption intentions. The fintech industry and the governments of Macao and Hengqin can work on improving technology's ease of use and usefulness. They can also promote them to Macao users, and provide the resources required for better access to fintech in the zone